The influence of social power on neural responses to emotional conflict - Ma, Xueling; Zhang, Entao (PeerJ, 2021)
Background Major power theories assume that social power can play an important role in an individual’s goal-related behaviors. However, the specific psychological mechanisms through which this occurs remain unclear. Some studies suggested that having power enhanced individuals’ goal-related behaviors, by contrast, other studies suggested that low-power individuals were associated with a greater performance in goal-directed tasks. We were particularly interested in how social power changes individuals’ goal-related behaviors during an emotional face-word Stroop task. Method Social power was primed by asking participants to recall a past situation in which they were in a position of power (high-power individuals), or a situation in which they were lacking power (low-power individuals). Afterward, participants were asked to complete an emotional face-word Stroop task. In the task, words representing specific emotions were written in a prominent red color across a face, and these words and facial expressions were either congruent or incongruent. The participant’s task was to judge the emotion of the face while ignoring the red emotional words. Results Our behavioral data showed that these individuals displayed faster reaction time and better accuracy in congruent conditions, slower reaction time for fearful faces and worse accuracy for happy faces in both incongruent and congruent conditions. The event-related potential analyses showed that, compared with low-power individuals, high-power individuals showed greater P1 amplitudes when faced with emotional stimuli (both incongruent and congruent conditions), indicating that power affects individuals’ attention in the early sensory processing of emotional stimuli. For the N170 component, low-power individuals showed more negative amplitudes when facing emotional stimuli, indicated that low-power individuals paid more attention to the construct information of emotional stimuli. For the N450 component, compared with congruent conditions, incongruent conditions elicited more negative amplitudes for both high- and low-power individuals. More importantly, fearful faces provoked enhanced P1 amplitudes in incongruent conditions than in congruent conditions only for low-power individuals, while, happy faces elicited larger P1 amplitudes in congruent conditions than in incongruent conditions only for high-power individuals. The findings suggested that during the initial stage of stimuli processing low-power individuals are more sensitive to negative stimuli than high-power individuals. Conclusion These findings provided electrophysiological evidence that the differences in the emotional conflict process between high- and low-power individuals mainly lies in the early processing stages of emotional information. Furthermore, evidence from P1 and N170 showed that there was also a redistribution of attentional resources in low-power individuals.
Keywords: Social power; Emotional conflict; Event-related potential; P1